Valorization of Wastewater Resources Into Biofuel and Value-Added Products Using Microalgal System - Arora, Kanika; Kaur, Parneet; Kumar, Pradeep; Singh, Archana; Patel, Sanjay Kumar Singh; Li, Xiangkai; Yang, Yung-Hun; Bhatia, Shashi Kant; Kulshrestha, Saurabh (Frontiers in Energy Research, 2021)
Wastewater is not a liability, instead considered as a resource for microbial fermentation and value-added products. Most of the wastewater contains various nutrients like nitrates and phosphates apart from the organic constituents that favor microbial growth. Microalgae are unicellular aquatic organisms and are widely used for wastewater treatment. Various cultivation methods such as open, closed, and integrated have been reported for microalgal cultivation to treat wastewater and resource recovery simultaneously. Microalgal growth is affected by various factors such as sunlight, temperature, pH, and nutrients that affect the growth rate of microalgae. Microalgae can consume urea, phosphates, and metals such as magnesium, zinc, lead, cadmium, arsenic, etc. for their growth and reduces the biochemical oxygen demand (BOD). The microalgal biomass produced during the wastewater treatment can be further used to produce carbon-neutral products such as biofuel, feed, bio-fertilizer, bioplastic, and exopolysaccharides. Integration of wastewater treatment with microalgal bio-refinery not only solves the wastewater treatment problem but also generates revenue and supports a sustainable and circular bio-economy. The present review will highlight the current and advanced methods used to integrate microalgae for the complete reclamation of nutrients from industrial wastewater sources and their utilization for value-added compound production. Furthermore, pertaining challenges are briefly discussed along with the techno-economic analysis of current pilot-scale projects worldwide.